Implementasi Pendidikan Karakter Berbasis Kearifan Lokal Cuci Negeri dalam Pembelajaran IPS - Bety D.S Hetarion; Yosina Hetarion; Vando Makaruku (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2020)
This article contains the inculcation of the value of local wisdom washing the country as part of character education in order to increase good character awareness of students at school. The aim is to strengthen the character of both students so that they can maintain social harmony both with fellow humans and with the environment through the behavior of daily life. This study uses a qualitative method with an ethnographic approach and Classroom Action Research according to Elliot (Wiriaatmadja, 2006), with a locus of research in the Hukurila community of Leitimur Selatan sub-district in Ambon city and Ambon 15 state junior high school. The results showed that the people of the country of Hukurila still preserve the local wisdom of washing the country that has virtue values ​​such as religious values, responsibility values, masohi values, democratic values ​​and care for the environment. These values ​​can be used as a source of social studies learning. Implementation in social studies shows the results that students can apply the values ​​of local wisdom in washing the country in social studies learning both in the classroom and outside the classroom.